A Critical Discourse Analysis of the Representation of Israel and Palestine in American Media - Markkula, Eveliina (My University, 2025)
This thesis studies how Israel and Palestine are represented in American media reports about the ongoing war in the Gaza Strip. Media can fundamentally affect views of the audience on current topics, so researching and increasing awareness of media bias is crucial. The data for this study come from four CNN articles and seven New York Post articles that were published in September 2024. This study applies Critical Discourse Analysis to investigate selected linguistic features in the materials. The purpose of this thesis is to examine how the lexical choices, transitivity structures, and arguments and claims in the materials are used to create representation of both sides of the conflict, and how they might reveal bias. The findings of this thesis reveal differences in representations of Israel and Palestine in all categories, most notably in the lexicon. Further research could be conducted to examine how different linguistic elements, such as narrative, are utilised to create representation.
Keywords: representation, critical discourse analysis, Israel, Palestine, media